2014
DOI: 10.1111/cogs.12190
|View full text |Cite
|
Sign up to set email alerts
|

Iconic Prosody in Story Reading

Abstract: Recent experiments have shown that people iconically modulate their prosody corresponding with the meaning of their utterance (e.g., Shintel et al., 2006). This article reports findings from a story reading task that expands the investigation of iconic prosody to abstract meanings in addition to concrete ones. Participants read stories that contrasted along concrete and abstract semantic dimensions of speed (e.g., a fast drive, slow career progress) and size (e.g., a small grasshopper, an important contract). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
35
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 61 publications
(42 citation statements)
references
References 41 publications
5
35
0
2
Order By: Relevance
“…For example, when producing the novel word 'seebow' to mean 'big', adults increased the duration and amplitude and decreased the fundamental frequency relative to when it meant 'small'. Adults have also been found to modify their prosody in iconic ways outside of child-directed communication, such as when reading short stories out loud (Perlman, Clark, & Johansson Falck, 2015; also see Shintel, Nusbaum, & Okrent, 2006). These studies focused on prosodic properties, but phonetic features like vocal quality and voicing may be altered as well.…”
Section: How Do Some Words Become More Iconic?mentioning
confidence: 99%
See 1 more Smart Citation
“…For example, when producing the novel word 'seebow' to mean 'big', adults increased the duration and amplitude and decreased the fundamental frequency relative to when it meant 'small'. Adults have also been found to modify their prosody in iconic ways outside of child-directed communication, such as when reading short stories out loud (Perlman, Clark, & Johansson Falck, 2015; also see Shintel, Nusbaum, & Okrent, 2006). These studies focused on prosodic properties, but phonetic features like vocal quality and voicing may be altered as well.…”
Section: How Do Some Words Become More Iconic?mentioning
confidence: 99%
“…Across the world's languages, there is a bias for words meaning 'small' to contain the high front vowel /i/ (Blasi, Wichmann, Hammarström, Stadler, & Christiansen, 2016). We know that speakers -and perhaps especially adults speaking with children -accentuate words for 'small' by raising their fundamental frequency (Nygaard et al, 2009;Perlman et al, 2015). It is also known that high vowels like /i/ tend to be articulated with a higher fundamental frequency than lower vowels (Whalen & Levitt, 1995), and high front vowels, in particular, are characterized by a maximum difference between the frequencies of the second and first formants (Ohala, 1994).…”
Section: How Do Some Words Become More Iconic?mentioning
confidence: 99%
“…For example, they inflected their pitch when reading stories about high location and upward movement versus low location and downward movement (Clark, Perlman, & Johansson Falck, 2014) and about small versus big size (Perlman, Clark, & Johansson Falck, 2015). They also modulated their articulation rate when reading stories about fast versus slow-paced events , and when providing spontaneous, open-ended descriptions of fast versus slow events viewed in short video clips (Perlman, 2010).…”
Section: Iconicity In Vocal Productionmentioning
confidence: 99%
“…Systematic auditory–visual mappings have been found in multiple domains, including between loudness and size (e.g., Smith & Sera, ), pitch and brightness (e.g., Marks, ; Melara, ; Mondloch & Maurer, ), pitch and shape (e.g., Marks, ), and pitch and visuo‐spatial height (e.g., Chiou & Rich, ). Evidence suggests that such correspondences are recruited in spoken language to convey visuo‐spatial properties of linguistic referents (e.g., Nygaard et al, ; Perlman et al, ; Shintel et al, ; Tzeng et al, ). For example, speakers spontaneously modulated their verbal descriptions of vertically moving dots such that descriptions of upward moving dots (e.g., “It is going up.”) were higher pitched than those of downward moving dots (Shintel et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…In addition to conveying information about speaker affective state, prosodic cues are encoded in representations of spoken words and affect lexical processing and speech production (e.g., Hupp & Jungers, 2013;Nygaard, Herold, & Namy, 2009;Perlman et al, 2015;Shintel & Nusbaum, 2008;Tzeng, Duan, Namy, & Nygaard, 2017;Wurm, Vakoch, Strasser, Calin-Jageman, & Ross, 2001). Nygaard et al (2009), for instance, found that speakers produced reliable prosodic cues to the meaning of novel adjectives (e.g., daxen, meaning small).…”
Section: Introductionmentioning
confidence: 99%